2021
DOI: 10.1007/s10899-021-10057-8
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Emotion Regulation Strategies in Adolescent Gamblers with and Without At-Risk Profiles

Abstract: Alexithymia, difficulties in emotion regulation, and negative affect play an important role in adolescents who present pathological gambling. Therefore, the objectives of the present study were, firstly, to analyze the differences between alexithymia, difficulties in emotion regulation, and positive and negative affect in adolescents with and without risk of gambling problems. Secondly, the relationships between all the variables of the study in adolescents with and without risk of problem gambling were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
1
6
0
1
Order By: Relevance
“…The variable of emotion regulation difficulties had a direct association with addictive tendencies, which is consistent with the results of previous studies (19,20). The general theory of addiction indicates that emotional dysregulation caused by cognitive-emotional dysregulation leads to problems such as the lack of emotional awareness and understanding, lack of correct acceptance of feelings, inability to manage affections, and discomfort and isolation (21).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The variable of emotion regulation difficulties had a direct association with addictive tendencies, which is consistent with the results of previous studies (19,20). The general theory of addiction indicates that emotional dysregulation caused by cognitive-emotional dysregulation leads to problems such as the lack of emotional awareness and understanding, lack of correct acceptance of feelings, inability to manage affections, and discomfort and isolation (21).…”
Section: Discussionsupporting
confidence: 89%
“…Emotional dysregulation is a set of conscious and unconscious strategies manifested as the inability to control and moderate emotional expression and causes incorrect re-appraisal of cognitive changes before the occurrence of emotion (17,18). Emotional dysregulation predisposes people to addictive behaviors (19). Previous studies demonstrated the effect of emotion regulation on addictive tendencies (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…The results support the hypothesized model and confirm the influence of alexithymia in problematic online gambling, both directly and indirectly, taking into account the partial mediation of dissociation and the moderation of cohesive family functioning. In other words, deficits in emotional processing and regulation may prevent gamblers from managing and containing internal distress, resulting in attempts at external regulation [18,69]. In mediating this relationship, dissociation can be seen as an extreme way to cope with dysregulated negative effects, further impeding their processing and awareness, thus fuelling external dysfunctional strategies, such as pathological online gambling [15,19,21].…”
Section: Discussionmentioning
confidence: 99%
“… 34 Previous studies have found that alexithymia may favor the use of dysfunctional emotion regulation as a way of increasing emotional arousal and avoiding negative emotions. 35 It was emphasized that approaches that deal with alexithymia and emotional dysregulation together can provide more positive results. 34 Similarly, in our study, we found that there was a significant correlation between ED and TAS scale scores.…”
Section: Discussionmentioning
confidence: 99%